Magnetic-pulse treatment of ring welded joints - S. V. Kabluchev; D. S. Perlov; D. V. Rogozin; E. L. Strizhakov (Advanced Engineering Research)
Introduction. The use of the magnetic-pulse treatment method which helps to eliminate and prevent annular seam defects is considered.Research Results. The method is developed for using magnetic-pulse alignment to eliminate deformations that are formed under welding and due to residual stresses. The welded seam is deformed and takes the position that fails to meet the product requirements. The result is local bending, which is 0.5−2.0 mm, and the diameter reduction in the annular seam area.Materials and Methods. Theoretical analysis is performed, and a practical research technique is tested. A twisted inductor for expansion and copper satellites for transmitting magnetic pressure are used for the experiments.Discussion and Conclusions. The workability of the magneticpulse treatment to eliminate and prevent deformations in the annular seams is determined. That makes it possible to align the annular seam remotely, or prestrain structural components ensuring for virtual deformation compensation before the welding. It is expedient to process pipes and rings of 100 mm in diameter with 2-5 mm WT by the current induction, and by the expansion technique.